Current trends in the use of informatics applied to business administration processes: Theoretical reflections - Cevallos-Ramos , Carina del Rocío; Naranjo-Vaca, Myriam Johanna; Vilcacundo-Reinoso, Galo Iván; Castelo-Salazar, Ángel Gerardo (Journal of the University of Zulia, 2024)
The growing digitalization of administrative processes is presented as an irreversible trend in the management of data processed at all times by public administration and private companies; In this context of rapid technological changes, the objective of the research was to determine current trends in the use of informatics applied to administration processes; objective that is justified by the reason that computing is the science of methods, techniques and processes to store, process and transmit information in digital format. Methodologically, the research was developed as an essay developed through the critical examination of documentary sources published in high-impact scientific journals and authoritative academic sources on the subject. The results obtained allow us to conclude that current trends in the use of computing in management processes are constantly evolving, focusing on artificial intelligence, cloud computing, automation and new generation computing. These technologies and tools have the potential to greatly improve decision making and empower companies’ employees.